Leaders’ Leadership Theory in a Management Perspective (American Journal of Multidisciplinary Research and Innovation, 2023)
Leadership is the most important characteristic of a manager. Leadership is a spiritual tool for the better use and organization of human activities, coordination, abilities and characteristics. The manager or leader has leadership resources. The basis of these sources may be formal and possibly informal, which is necessary to understand. There are various institutions in the political, cultural, social and economic spheres of societies; Each of these employees has different characteristics and different qualifications, which need to be studied so that organizations and institutions can develop well. To this end, the ability to lead has been researched by managing science researchers. A manager has different solutions to achieve the goal to solve his problems better and reach the goal on a regular basis. These solutions are the various theories that have been developed by the science researchers. Management science researchers have already clarified the logical approach of any solution or theory for a manager or leader, highlighting the advantages and disadvantages, which makes it much easier for a manager to lead.